ASSESSING THE IMPACT OF MICROPLASTIC ACCUMULATION ON MARINE BIODIVERSITY AND HUMAN FOOD SECURITY IN COASTAL URBAN REGOINS - Khoironi Fanana Akbar; Syafiq Amir; Thabo Mokoena (Research of Scientia Naturalis, 2026)
Accelerating urbanization and increasing plastic consumption have intensified microplastic contamination in coastal environments, raising serious concerns about marine ecosystem degradation and human food security. Persistent microplastic accumulation threatens marine biodiversity through bioaccumulation, trophic transfer, habitat deterioration, and physiological stress while contaminating commercially important seafood species. This study evaluated the ecological impacts of microplastic accumulation on marine biodiversity and food security across coastal urban regions by examining interactions among environmental contamination, ecosystem resilience, fisheries productivity, seafood safety, and environmental governance. A mixed-methods sequential explanatory design was employed using environmental monitoring data from 72 coastal monitoring stations across twelve urban coastal regions. Quantitative analyses included biodiversity assessment, laboratory characterization of microplastics, multivariate statistics, structural equation modeling, hierarchical regression, mediation, and moderation analyses, while qualitative evidence was analyzed through thematic analysis. Findings revealed that increasing microplastic accumulation significantly reduced marine biodiversity, weakened ecosystem resilience, decreased fisheries productivity, and increased seafood contamination. Biodiversity integrity partially mediated environmental contamination and fisheries productivity, whereas environmental governance enhanced ecological resilience through improved waste management and integrated coastal management, supporting long-term ecosystem sustainability and food security in rapidly urbanizing coastal regions.